Enhancing Attention Through Contextual Creative Art Activities: A Case Study of Early Childhood Learners in a Southern Border School of Thailand - Ummah Tohlong, Ummul; Bukehmatee, Nurnee; Baru, Muhammadzofree (Journal of Information System and Education Development, 2025)
This quasi-experimental classroom action research examined the effectiveness of creative art activities in enhancing attention among early childhood learners in Thailand's southern border provinces. The sample consisted of five kindergarten (K3) students from Ban Yaring School in Pattani Province, selected via purposive sampling based on preliminary attention assessments. Over a period of three months, participants engaged in 12 creative art sessions specifically designed to be developmentally appropriate and culturally relevant to the local Muslim context. Quantitative findings revealed a statistically significant improvement in children's attention levels (p < .05). Qualitative observations and interviews further indicated that children could concentrate on tasks for longer durations, exhibited better self-control, and parents reported a noticeable reduction in unnecessary screen time at home—demonstrating concrete positive changes in daily behavior. The study suggests that contextually relevant, age-appropriate creative art activities can serve as an effective tool for fostering attention development in young children, particularly within multicultural settings characterized by ethnic, religious, and linguistic diversity.